(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Interprofessional education (IPE) has gained recognition as a crucial component in healthcare training, aiming to foster collaboration and teamwork among various healthcare professionals. In the context of diabetes management, where multidisciplinary care is essential for optimal patient outcomes, understanding the impact of IPE on doctor-nurse collaboration is paramount. This article explores the current landscape of IPE initiatives in diabetes care and examines their influence on the collaborative relationship between doctors and nurses. Drawing upon existing literature and case studies, it highlights the benefits, challenges, and strategies for enhancing doctor-nurse collaboration through interprofessional education. By elucidating the impact of IPE on diabetes management, this article aims to provide insights for educators, healthcare administrators, and clinicians seeking to optimize collaborative practices in diabetes care.